Nature and Modernity in Edouard Manet's Le Dejeuner sur l'Herbe and William Holman Hunt's The Awakening Conscience: a Comparative and Critical Reading - Lin Chang (ITB Journal Publisher, LPPM ITB, 2019)
The painting Le Dejeuner sur l'Herbe (The Luncheon on the Grass) (1863) by the French artist Edouard Manet (1832-1883) received negative comments for the awkward nude and the puzzling narratives in the painting. After much debate, this work is now considered representative of both the artist's oeuvre and of the French modern art movement after the 1850s. While Manet and his fellow Impressionists provided their definition of modern art through their quick brushwork representing speed and light, English art from the same period needs its own definition. A Pre-Raphaelite artist, William Holman Hunt (1827-1910), through the painstaking techniques that characterize the style of the group, presented his version of modern art. In his The Awakening Conscience, a mistress is shown stunned by the sunlight and struggling to wake up her conscience. This paper juxtaposes the two paintings and explores two aspects of the paintings that have rarely been discussed and compared before: modernity and Nature. It was investigated how, in both paintings, Nature (as visualized through the image of greenery) is exploited by modern society and how the bourgeois protagonists relate themselves to Nature. In doing so, this paper provides an interpretation of the cultural and social significance of both art works.